A study on housing affordability in a Malaysian context / Nurul Edryn Zuraimi - Zuraimi, Nurul Edryn (Faculty of Communication and Media Studies, 2019)
Everyone will eventually get to the age where they have to buy a house. It is impossible that no one could have no problem at all when buying a house. But while they are struggling buying a house, what about the developers? housing glut can happen and it may as well be a loss towards the developers. When it comes to financial, the commitment towards buying a house is really tough. When it comes to financial, the commitment towards is really tough. They need to think: about their families, basic necessities, loans and many other commitments can lead to financial pressure In Maslow's Hierarchy of Needs, the lowest level of needs is physiological which are air, food, drink, shelter, warmth, sex, sleep and others. In relation to housing affordability, even though it is in the lowest level of needs, it is still crucial for a family to have a shelter. The respondents for this study are 200 Malaysians aged from 18 to 50 and above. The data is collected through an online survey with a total of 42 close-ended questions while the raw data collected is analysed using Statistical Package for Social Science (SPSS). finding found that only one out of the five hypothesis is accepted which is the expectancy of the house they want at β=O.341.